2023
DOI: 10.3390/app13031462
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Characterization of Single-Cracked Space Based on Microcrack Distribution in Sandstone Failure

Abstract: To further understand the rock damage zone, an approach based on microcrack distribution was proposed to characterize the crack space of rock specimens in this research. Acoustic emission (AE) technology was utilized on sandstone to obtain the spatial distribution of microcracks in which uniaxial compression forms the single-cracked fracture. The proposed theoretical distribution pattern space (TDPS), 3D convex hull, and the minimum volume enclosing ellipsoid (MVEE) algorithms were adopted to analyze the geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Panteleev et al [8] researched the micro mechanisms of granite fracture during three-point bending and found that during threepoint bending of granite, AE events are localized in the zone of formation of the future main crack. Hou et al [9] used AE to analyze sandstone and obtained the spatial distribution of micro-cracks formed due to uniaxial compression. Damaskinskaya et al [10] analyzed the spatial distribution of hypocenters of AE signal sources, and revealed that the transition to correlated defect formation occurs in some regions in the case of continuous electrical exposure, despite the accumulation of almost uniform spatial defect.…”
Section: Introductionmentioning
confidence: 99%
“…Panteleev et al [8] researched the micro mechanisms of granite fracture during three-point bending and found that during threepoint bending of granite, AE events are localized in the zone of formation of the future main crack. Hou et al [9] used AE to analyze sandstone and obtained the spatial distribution of micro-cracks formed due to uniaxial compression. Damaskinskaya et al [10] analyzed the spatial distribution of hypocenters of AE signal sources, and revealed that the transition to correlated defect formation occurs in some regions in the case of continuous electrical exposure, despite the accumulation of almost uniform spatial defect.…”
Section: Introductionmentioning
confidence: 99%